Shifting Livelihoods of Farmers in Namlea City - Umanailo, Rosita; Nawawi, Mansyur; Lisaholit, Syafa; Umanailo, Muhamad Chairul Basrun (Universitas Muhammadiyah Ponorogo, 2026)
As a result of land conversion into infrastructure development areas, cultivated land in Namlea Village has decreased which hurts farmers' ability to earn a living. Changes in land function are the primary source of problems because they reduce farmers' production. This study aimed to determine how farmers' efforts to diversify sources of income and adapt to urban changes have affected their agricultural land. This study uses a qualitative approach, and the number of informants to be interviewed was 18 people, who were interviewed purposefully. The informants surveyed in Namlea Village, Buru Regency, were farmers, housewives, community leaders, traditional leaders, and religious leaders. The data for this study were collected through in-depth interviews and observation methods. This study concluded that the shift in farmers' livelihoods as an impact of land conversion is carried out so that farmers' productivity is decreasing, as well as farmers'. To overcome the effect of land conversion in Namlea Village, the efforts needed are to encourage diversification of farmers' income through side business training, develop sustainable agribusiness, and provide access to capital and technology for production efficiency and wise land use planning, community empowerment in decision making, and social protection programs for farmers are also important.